Feminine Men and Gender-Fluid Identities on Social Media: A Thematic Exegesis of QS. An-Nisa [4]:1 and Ar-Rum [30]:30 - Kafi Kadhafi Ahmad; Sulidar Ujang (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
The growing use of social media has increased the visibility of feminine male expressions and gender-fluid identities while generating debate about their relationship to Islamic teachings. This study analyzes these phenomena through a thematic interpretation of Q.S. al-Nisā’ [4]: 1 and Q.S. al-Rūm [30]: 30. It employed qualitative library research and thematic exegesis (tafsir mawdū‘ī). Primary data comprised the two Qur’anic verses and their interpretations in selected classical and contemporary commentaries, while secondary data were drawn from books and journal articles on gender and social media. The data were analyzed by examining the concepts of human creation, common origin, fitrah, equal dignity, and moral responsibility; comparing exegetical perspectives; and relating the resulting synthesis to identity construction in digital spaces. The findings show that Q.S. al-Nisā’ [4]: 1 emphasizes humanity's common origin and equal dignity, whereas Q.S. al-Rūm [30]: 30 presents fitrah primarily as an innate orientation toward divine truth and moral values. Although neither verse directly addresses contemporary categories of gender identity, their interpretations offer an ethical framework for responding to gender expression on social media. This framework combines respect for human dignity and rejection of ridicule and violence with critical attention to the roles of social environment, popular culture, digital communities, and media platforms in identity formation. The study contributes to contemporary thematic Qur’anic studies by connecting classical and modern exegesis with gender-related phenomena in digital society.